THE RELATIONSHIP OF WEIGHT INCREASE WITH PREECLAMPSIA INCIDENCE IN TRIMESTER III PREGNANT WOMEN AT CURAHTULIS HEALTH CENTER - Ismatul Karimah; Titik Suhartini; Mega Silvian Natalia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Weight gain is one of the predisposing factors for the incidence of preeclampsia in pregnant women. The habit of eating fatty and salty foods is often associated with blood pressure because excess fat consumption can trigger atherosclerosis which is a factor causing hypertension, while excessive salt consumption can increase fluid accumulation in the blood (diuretics) which causes impaired blood circulation so that the heart will work stronger and eventually a person's blood pressure will be high. Preeclampsia is hypertension that occurs after 20 weeks of gestation accompanied by proteinuria, Preeclampsia in pregnancy-specific hypertensive disease with multisystem involvement.The purpose of the study was to analyze the relationship between weight gain and the incidence of preeclampsia in third trimester pregnant women at the CurahTulis Health Center, Tongas District, Probolinggo Regency. The research design used was a cross-sectional study with a retrospective time approach. The population in this study were 30 third trimester pregnant women and 30 third trimester pregnant women with preeclampsia. The sampling technique used a random sample. Collecting data using a questionnaire then the data is processed using SPSS using the Spearman rank test. The results of the analysis found that 9 pregnant women with excess body weight had a 100% risk of preeclampsia. while those with less or normal weight have a lower risk of developing preeclampsia. The results of the analysis of the significance value or Sig. (2-tailed) of 0.001, because the value of Sig. (2-tailed) 0.001 < less than 0.05, it means that there is a significant relationship between the variable weight gain and the incidence of preeclampsia in pregnant women. It is hoped that the Cultivation Health Center will be able to conduct socialization to the local community regarding the risk factors for preeclampsia in pregnant women.